TERAPI KESEHATAN DENGAN SAFAR DALAM PERSPEKTIF HADIS STUDI TERHADAP KITAB MUSNAD IMAM AHMAD BIN HANBAL - Daulay, Toharuddin (SHAHIH (Jurnal Ilmu Kewahyuan), 2021)
Humans as social beings certainly do a lot of activities to meet their needs. Starting from doing activities that are primary and secondary. In addition, in carrying out their activities, humans often feel bored, lazy, bored and so on. It is in situations like this that many of them fill their spare time and holidays by doing refreshments, touring, traveling, and the like. And in this day and age, recreation, traveling has even become a job or profession for some people. The Holy Qur'an is one of the extraordinary gifts bestowed by Allah to the glorious Prophet Muhammad SAW in which there is a beautiful and unique language. One of the features in the holy book of the Qur'an which at the same time shows the miracles of the language of the Qur'an is the choice of diction in it.